Lithium secondary battery separator and lithium secondary battery

JP7641585B2Active Publication Date: 2025-03-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021554304
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-25
Filing Date
2020-10-13
Publication Date
2025-03-07
Estimated Expiration
2040-10-13

Smart Images

  • Figure 0007641585000001
    Figure 0007641585000001
  • Figure 0007641585000002
    Figure 0007641585000002
  • Figure 0007641585000003
    Figure 0007641585000003
Patent Text Reader

Abstract

An aluminum foil comprising an aluminum foil substrate that has a porous region, wherein the porous region is formed throughout the entirety of the aluminum foil substrate in the thickness direction thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to lithium secondary batteries. [Background technology]

[0002] 2. Description of the Related Art Lithium secondary batteries, which include a positive electrode, a negative electrode, and an electrolyte, and perform charging and discharging by transferring lithium ions between the positive electrode and the negative electrode, are widely used as high-output, high-energy density secondary batteries.

[0003] As an example of a negative electrode material for lithium secondary batteries, aluminum is known, which can absorb lithium by being alloyed with lithium (see, for example, Patent Document 1).

[0004] Therefore, although it is possible to use aluminum foil as the negative electrode of a lithium secondary battery, the aluminum foil expands and contracts significantly during charging and discharging, causing damage such as wrinkles and breakage to the aluminum foil, resulting in, for example, a problem of a deterioration in the charge-discharge cycle characteristics of the lithium secondary battery.

[0005] Further, conventional lithium secondary batteries have a lithium ion-permeable separator interposed between the positive electrode and the negative electrode.

[0006] Meanwhile, separators using materials capable of absorbing lithium ions have been proposed (see, for example, Patent Documents 2 and 3). In Patent Document 2, aluminum foil is used as the separator, but the aluminum foil is non-porous and has low lithium ion permeability. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] U.S. Patent No. 4,002,492 [Patent Document 2] Japanese Patent Application Publication No. 8-180853 [Patent Document 3] JP 2010-219012 A Summary of the Invention

[0008] The aluminum foil according to one embodiment of the present disclosure has an aluminum foil base material having a porous region, and the porous region is formed throughout the thickness direction of the aluminum foil base material.

[0009] According to the aluminum foil of the present disclosure, when used as a negative electrode of a lithium secondary battery, it is possible to suppress the deterioration of the charge-discharge cycle characteristics. In addition, the aluminum foil of the present disclosure has lithium ion permeability and can be used as a separator of a lithium secondary battery. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the aluminum foil according to this embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the aluminum foil according to this embodiment. [Diagram 3] FIG. 3 is a cross-sectional SEM photograph showing another example of the aluminum foil according to this embodiment. [Figure 4] FIG. 4 is a diagram showing an example of an aluminum foil manufacturing apparatus according to this embodiment. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing an example of the lithium secondary battery of this embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view showing an example of the lithium secondary battery of this embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view showing another example of a battery structure in which the aluminum foil of the present embodiment is used as a separator. [Figure 8] FIG. 8 is a schematic cross-sectional view showing another example of a battery structure in which the aluminum foil of the present embodiment is used as a separator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] An example of an aluminum foil according to one embodiment of the present disclosure, a lithium secondary battery using the aluminum foil according to one embodiment of the present disclosure as a negative electrode, and a lithium secondary battery using the aluminum foil according to one embodiment of the present disclosure as a separator will be described below. The drawings referred to in the following description of the embodiments are schematic, and the dimensional ratios of the components depicted in the drawings may differ from the actual ones. In addition, in this specification, the expression "numerical value (1) to numerical value (2)" means numerical value (1) or more and numerical value (2) or less.

[0012] <Aluminum foil> FIG. 1 is a schematic cross-sectional view showing an example of an aluminum foil according to this embodiment. The aluminum foil 100 according to this embodiment has an aluminum foil base material 100a having a porous region 100b. The porous region 100b is formed in the entire thickness direction of the aluminum foil base material 100a. The porous region 100b has continuous pores in which a plurality of pores are intricately connected in the thickness direction. It is not necessary that all of the pores present in the porous region 100b are completely connected, and independent pores in a non-connected state may be included. In any case, the electrolyte solution permeates into the porous region 100b, and lithium ions in the electrolyte solution pass through the porous region 100b. That is, the aluminum foil 100 according to this embodiment has ion permeability and can be used as a separator for a lithium secondary battery. In addition, if the aluminum foil 100 is used as the negative electrode of a lithium secondary battery, absorption of lithium ions occurs on the surface of the aluminum foil 100 or inside the porous region 100b during charging, and the absorbed lithium ions are released during discharging. The expansion and contraction of the aluminum foil 100 accompanying the absorption and release of lithium ions is alleviated by the porous region 100b, thereby suppressing damage to the aluminum foil 100. As a result, the deterioration of the charge-discharge cycle characteristics of the lithium secondary battery is suppressed compared to an aluminum foil 100 that does not have the porous region 100b.

[0013] The aluminum foil base material 100a has a plurality of porous regions 100b formed therein, for example, at intervals in the surface direction of the aluminum foil base material 100a.

[0014] It is preferable that an Al-Li alloy is present in the porous region 100b. Specifically, at least a part of the aluminum foil base material 100a in the porous region 100b is an Al-Li alloy. In this way, the presence of the Al-Li alloy in the porous region 100b increases the lithium ion conductivity of the porous region 100b. Therefore, when the aluminum foil 100 in which the Al-Li alloy is present in the porous region 100b is used as a negative electrode or a separator, it is possible to improve the battery characteristics of a lithium secondary battery.

[0015] FIG. 2 is a schematic cross-sectional view showing another example of the aluminum foil according to this embodiment, and FIG. 3 is a cross-sectional SEM photograph showing another example of the aluminum foil according to this embodiment. As shown in FIG. 2 and FIG. 3, the aluminum foil 100 according to this embodiment has an Al-Li alloy layer 100c arranged on one side of the aluminum foil base material 100a so as to cover the porous region 100b. In the aluminum foil 100 having such a structure, the electrolyte penetrates into the porous region 100b from one side of the aluminum foil base material 100a and reaches the other side, but the solvent in the electrolyte is blocked by the Al-Li alloy layer 100c, so that the aluminum foil 100 hardly penetrates the aluminum foil 100. However, since the lithium ions in the electrolyte can penetrate the Al-Li alloy layer 100c, the aluminum foil 100 has lithium ion permeability. Although the explanation in the figure is omitted, the aluminum foil 100 according to this embodiment may have an Al-Li alloy layer 100c arranged on both sides of the aluminum foil base material 100a so as to cover the porous region 100b. Even when the aluminum foil 100 has an Al-Li alloy layer 100c on both sides, lithium ions enter the porous region 100b through one of the Al-Li alloy layers 100c, and lithium ions in the porous region 100b move out of the porous region 100b through the other Al-Li alloy layer 100c. Therefore, the aluminum foil 100 having the Al-Li alloy layer 100c arranged so as to cover the porous region 100b on one or both sides of the aluminum foil base material 100a has ion permeability and can be used as a separator for a lithium secondary battery. In addition, by using the aluminum foil 100 having the Al-Li alloy layer 100c arranged so as to cover the porous region 100b on one or both sides of the aluminum foil base material 100a as a negative electrode, the porous region 100b can be efficiently used as a reaction region with lithium, which may improve the battery characteristics.

[0016] By the way, in a two-liquid lithium battery using a positive electrode electrolyte as the electrolyte in contact with the positive electrode and a negative electrode electrolyte as the electrolyte in contact with the negative electrode, the optimum electrolyte can be used for each of the positive and negative electrodes, so that it is possible to achieve high energy density, high durability, and high output of the lithium secondary battery. In such a two-liquid lithium battery, if a separator through which the solvent in the electrolyte can easily pass is used, the solvent in the positive electrode electrolyte will move through the separator to the negative electrode side and be reduced and decomposed, and the solvent in the negative electrode electrolyte will move through the separator to the positive electrode side and be oxidized and decomposed, so that the advantage of using two electrolytes for the electrolyte cannot be obtained. However, in the case of the aluminum foil according to this embodiment, the porous region 100b is a continuous pore in which a plurality of pores are intricately connected in the thickness direction, so that the structure is such that the solvent in the electrolyte is difficult to pass through. In particular, in the case of an aluminum foil 100 having an Al-Li alloy layer 100c arranged on one or both sides of an aluminum foil base material 100a so as to cover a porous region 100b, as described above, the solvent in the electrolyte can hardly penetrate the aluminum foil 100. Therefore, since the aluminum foil 100 of this embodiment can separate the electrolyte for the positive electrode and the electrolyte for the negative electrode, it can also be used as a separator for a two-liquid lithium secondary battery. In addition, in a conventional resin separator, the solvent in the electrolyte easily passes through the pores of the separator, so it is difficult to separate the electrolyte for the positive electrode and the electrolyte for the negative electrode.

[0017] The thickness of the aluminum foil base 100a is appropriately set depending on whether it is used as a separator or a negative electrode, but in order to ensure the strength and flexibility of the aluminum foil 100, the thickness is preferably in the range of 1 μm to 200 μm, and more preferably in the range of 5 μm to 150 μm.

[0018] The average pore size of the pores constituting the porous region 100b is appropriately set depending on whether the material is used as a separator or a negative electrode, etc., but in terms of ensuring the strength and flexibility of the aluminum foil 100, for example, the average pore size is preferably in the range of 0.0001 μm to 10 μm, and more preferably in the range of 0.001 μm to 5 μm.

[0019] The Al-Li alloy layer 100c may be formed on one or both entire surfaces of the aluminum foil substrate 100a.

[0020] <Method of manufacturing aluminum foil 100> FIG. 4 is a schematic diagram showing an example of an aluminum foil manufacturing apparatus according to this embodiment. The manufacturing apparatus 1 shown in FIG. 4 has an electrolytic cell 13 having a first chamber 10 and a second chamber 11, an electrolytic solution (14, 15) filled in the first chamber 10 and the second chamber 11, a counter electrode 16 immersed in the electrolytic solution 14 in the first chamber 10, and a counter electrode 17 immersed in the electrolytic solution 15 in the second chamber 11. The counter electrode 16 in the first chamber 10 and the counter electrode 17 in the second chamber 11 are lithium metal. The electrolytic solution (14, 15) filled in the first chamber 10 and the second chamber 11 contains a lithium salt and an organic solvent. The electrolytic solutions (14, 15) filled in the first chamber 10 and the second chamber 11 may have the same composition or different compositions.

[0021] When manufacturing the aluminum foil according to this embodiment, the aluminum foil base material 18 is placed between the first chamber 10 and the second chamber 11 so that the first chamber 10 and the second chamber 11 do not communicate with each other, and the first chamber 10 and the second chamber 11 are filled with the electrolytic solution (14, 15), and each electrode is placed. That is, one surface of the aluminum foil base material 18 contacts the electrolytic solution 14 in the first chamber 10, and the opposite surface of the aluminum foil base material 18 contacts the electrolytic solution 15 in the second chamber 11. Then, the counter electrode 16 in the first chamber 10 and the aluminum foil base material 18 are electrically connected to pass a reduction current through one surface of the aluminum foil base material 18, and the counter electrode 17 in the second chamber 11 and the aluminum foil base material 18 are electrically connected to pass an oxidation current through the opposite surface of the aluminum foil base material 18. As a result, an Al-Li alloy is formed on one side of the aluminum foil substrate 18 by the reduction current, and aluminum is dissolved on the opposite side of the aluminum foil substrate 18 by the oxidation current. By continuing this process for a predetermined time, a porous region is formed in the entire thickness direction of the aluminum foil substrate 18, an Al-Li alloy is formed in the porous region, and an Al-Li layer is formed on one side of the aluminum foil substrate 18 so as to cover the porous region. In addition, after a reduction current is passed through one side of the aluminum foil substrate 18 to form an Al-Li alloy, a reduction current is passed through the opposite side of the aluminum foil substrate 18 to form an Al-Li alloy, thereby obtaining an aluminum foil having an Al-Li alloy layer formed on both sides of the aluminum foil substrate 18. Note that, even if an oxidation current is only passed through one side of the aluminum foil substrate 18, an aluminum foil having a porous region formed throughout the entire thickness direction of the aluminum foil substrate 18 can be obtained. Here, from the viewpoint of uniformity in the thickness direction of the porous region, it is preferable to pass an oxidation current simultaneously from both sides of the aluminum foil substrate 18.

[0022] The reduction current density on one side of the aluminum foil substrate 18 is, for example, 1 μA / cm 2 ~100mA / cm 2 The oxidation current density on the opposite side of the aluminum foil substrate 18 is, for example, 10 μA / cm 2 ~1000mA / cm2 The time for which the reducing current and the oxidizing current are applied (treatment time) is, for example, in the range of 1 millisecond to 1000 hours.

[0023] The lithium salt contained in the electrolyte (14, 15) filled in the first chamber 10 and the second chamber 11 can be a known lithium salt used in electrolytes for lithium secondary batteries, for example, LiPF 6 The organic solvent contained in the electrolyte (14, 15) filled in the first chamber 10 and the second chamber 11 may be a known organic solvent used in electrolytes for lithium secondary batteries, and examples of such organic solvents include cyclic carbonate esters such as propylene carbonate (PC), cyclic carboxylate esters such as γ-butyrolactone, and chain carboxylate esters such as methyl acetate.

[0024] <Lithium secondary battery using the aluminum foil of this embodiment as the negative electrode> Fig. 5 is a schematic cross-sectional view showing an example of the lithium secondary battery of this embodiment. The lithium secondary battery 20 shown in Fig. 5 includes a cup-shaped battery case 21, an electrode body having a positive electrode 22, a negative electrode 23, a separator 24 provided between the positive electrode 22 and the negative electrode 23, a gasket 25 formed of an insulating material, and a sealing plate 26 disposed at the opening of the battery case 21 and sealing the battery case 21 via the gasket 25. In the lithium secondary battery 20 shown in Fig. 5, the space between the positive electrode 22 and the negative electrode 23 is filled with an electrolyte 27. The lithium secondary battery 20 shown in Fig. 5 is a so-called coin type or button type, but the shape of the lithium secondary battery of this embodiment is not particularly limited, and may be, for example, a cylindrical type, a flat type, a square type, a laminate type, or the like. In addition, the electrode body including the positive electrode 22, the negative electrode 23, and the separator 24 may be, for example, a wound electrode body in which the positive electrode and the negative electrode are wound with the separator interposed therebetween, or a laminated electrode body in which the positive electrode and the negative electrode are alternately laminated with the separator interposed therebetween.

[0025] The positive electrode 22 includes, for example, a positive electrode current collector and a positive electrode composite layer formed on the positive electrode current collector. As the positive electrode current collector, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface layer, can be used. From the viewpoint of current collecting properties, mechanical strength, etc., the thickness of the positive electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.

[0026] The positive electrode mixture layer includes a positive electrode active material and may also include a binder, a conductive material, and the like.

[0027] Examples of the positive electrode active material include lithium transition metal oxides containing lithium (Li) and transition metal elements such as cobalt (Co), manganese (Mn) and nickel (Ni). Other examples of the positive electrode active material include transition metal sulfides, metal oxides, and lithium iron phosphate (LiFePO 4 ) and lithium iron pyrophosphate (Li 2 FeP 2 O 7 Lithium-containing polyanion compounds containing one or more transition metals such as sulfur-based compounds (Li 2 S), oxygen, and oxygen-containing metal salts such as lithium oxide. The positive electrode active material is preferably a lithium-containing transition metal oxide, which preferably contains at least one of Co, Mn, and Ni as a transition metal element.

[0028] The lithium transition metal oxide may contain additional elements other than Co, Mn, and Ni, such as aluminum (Al), zirconium (Zr), boron (B), magnesium (Mg), scandium (Sc), yttrium (Y), titanium (Ti), iron (Fe), copper (Cu), zinc (Zn), chromium (Cr), lead (Pb), tin (Sn), sodium (Na), potassium (K), barium (Ba), strontium (Sr), calcium (Ca), tungsten (W), molybdenum (Mo), niobium (Nb), and silicon (Si).

[0029] Specific examples of lithium transition metal oxides include Li x Chief of Staff2 , Li x , NiO 2 , Li x , MnO 2 , Li x , Co y , Ni 1-y , O 2 , Li x , Co y , M 1-y , O z , Li x , Ni 1-y , M y , O z , Li x , Mn 2 , O 4 , Li x , Mn 2-y , M y , O 4 , LiMPO 4 , Li 2 , MPO 4 (In each chemical formula, M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3). The lithium transition metal oxide may be used alone or in combination of multiple types. From the viewpoint of increasing the capacity, it is preferable that the lithium transition metal oxide contains 80 mol% or more of Ni with respect to the total amount of transition metals other than lithium. Also, from the viewpoint of the stability of the crystal structure, it is more preferable that the lithium transition metal oxide is Li a , Ni b , Co c , Al d , O 2 (0 < a ≤ 1.2, 0.8 ≤ b < 1, 0 < c < 0.2, 0 < d ≤ 0.1, b + c + d = 1).

[0030] As the conductive material, a known conductive material that enhances the electrical conductivity of the positive electrode mixture layer can be used, and examples of such materials include carbon materials such as carbon black, acetylene black, ketjen black, graphite, carbon nanofibers, carbon nanotubes, and graphene. As the binder, a known binder that maintains good contact between the positive electrode active material and the conductive material and enhances the binding of the positive electrode active material to the positive electrode current collector surface can be used, and examples of such binders include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, carboxymethylcellulose (CMC) or a salt thereof, styrene-butadiene rubber (SBR), polyethylene oxide (PEO), polyvinyl alcohol (PVA), and polyvinylpyrrolidone (PVP).

[0031] The positive electrode 22 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, etc. onto a positive electrode current collector, drying and rolling the coating, and forming a positive electrode mixture layer on the positive electrode current collector.

[0032] The aluminum foil of this embodiment is used for the negative electrode 23. That is, the aluminum foil having an aluminum foil base material having a porous region formed in the entire thickness direction is used for the negative electrode 23. As described above, the porous region formed in the aluminum foil base material alleviates the expansion and contraction caused by the absorption and release of lithium ions, so that damage to the negative electrode 23 (aluminum foil) is suppressed. As a result, the deterioration of the charge and discharge cycle characteristics of the lithium secondary battery 20 is suppressed.

[0033] In addition, it is preferable that an Al-Li alloy is present in the porous region, which increases the lithium ion conductivity of the porous region, and may improve the battery characteristics of the lithium secondary battery 20. Specifically, the initial capacity of the lithium secondary battery may be improved.

[0034] In addition, it is preferable that an Al-Li alloy layer is disposed on one or both sides of the aluminum foil substrate so as to cover the porous region. This allows the porous region to be efficiently used as a reaction region with lithium, which may improve the battery characteristics. Specifically, the initial capacity of a lithium secondary battery may be improved. An aluminum foil having an Al-Li alloy layer disposed on one side of the aluminum foil substrate is used as a negative electrode, and Li x Chief of Staff 2 When a lithium transition metal oxide such as is used as the positive electrode active material, it is preferable to arrange the negative electrode (aluminum foil) so that the surface of the aluminum foil base material on which the Al-Li alloy layer is not arranged faces the positive electrode 22 via the separator 24. This makes it easier for lithium ions to move into the porous region, which may improve the battery characteristics.

[0035] The thickness of the aluminum foil substrate is, for example, preferably in the range of 10 μm to 200 μm, and more preferably in the range of 50 μm to 150 μm, from the viewpoint of improving battery characteristics while ensuring the strength and flexibility of the aluminum foil.

[0036] The average pore size of the pores constituting the porous region is, for example, preferably in the range of 0.1 μm to 10 μm, and more preferably in the range of 0.5 μm to 5 μm, from the viewpoint of improving battery characteristics while ensuring the strength and flexibility of the aluminum foil.

[0037] The separator 24 may be, for example, a porous sheet that allows lithium ions to pass through. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. Examples of the material of the porous sheet include olefin resins such as polyethylene and polypropylene, polyamide, polyamideimide, and cellulose. The porous sheet may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. The porous sheet may also be a multilayer body including a polyethylene layer and a polypropylene layer, and may be a porous sheet having a surface coated with a material such as an aramid resin or ceramic. The separator 24 may be the aluminum foil of this embodiment, as described later.

[0038] The electrolytic solution contains a solvent and an electrolyte salt dissolved in the solvent. Note that a gel electrolyte such as a gel polymer may be used instead of the electrolytic solution.

[0039] Examples of the solvent that can be used include carbonates, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these. The solvent may contain a halogen-substituted product in which at least a portion of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.

[0040] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0041] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, and the like. and chain ethers such as ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0042] As the halogen-substituted compound, it is preferable to use a fluorinated cyclic carbonate such as fluoroethylene carbonate (FEC), a fluorinated chain carbonate, a fluorinated chain carboxylate such as methyl fluoropropionate (FMP), or the like.

[0043] The electrolyte salt is LiClO 4 , LiBF 4 , LiPF 6 , LiAlCl 4 , LiSbF 6 , LiSCN, LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiB 10 Cl 10 , lithium lower aliphatic carboxylate, LiCl, LiBr, LiI, Li(P(C 2 O 4 )F4 )), LiPF 6-x (C n F 2n+1 ), x (1 < x < 6, n is 1 or 2), lithium chloroborane, borates, imide salts, etc. Examples of borates include Li[B(C 2 O 4 ) 2 , Li[B(C 2 O 4 )F 2 , Li 2 B 4 O 7 , lithium bis(1,2-benzenediolate(2-)-O,O’)borate, lithium bis(2,3-naphthalenediolate(2-)-O,O’)borate, lithium bis(2,2’-biphenyldiolate(2-)-O,O’)borate, lithium bis(5-fluoro-2-olate-1-benzenesulfonate-O,O’)borate, etc. Examples of imide salts include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(perfluoroethanesulfonyl)imide (LiBETI), lithium (perfluoroethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide (LiFTI), etc. Among these, in terms of battery characteristics, LiPF 6 , LiTFSI, LiBF 4 , LiSbF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 are preferred. The electrolyte salt may be used alone or in combination of multiple kinds. The concentration of the electrolyte salt is preferably, for example, 0.5 to 3 mol / L, and more preferably 0.8 to 1.8 mol / L.

[0044] <Lithium secondary battery using aluminum foil of this embodiment as separator> Fig. 6 is a schematic cross-sectional view showing an example of a lithium secondary battery according to the present embodiment. The lithium secondary battery 30 shown in Fig. 6 includes a positive electrode 32, a negative electrode 33, separators 34 arranged with a gap between the positive electrode 32 and the negative electrode 33, a positive electrode electrolyte 36, a negative electrode electrolyte 38, and a container 40.

[0045] In the lithium secondary battery 30 shown in FIG. 6, the inside of a container 40 is separated by a separator 34 into a positive electrode chamber 42 and a negative electrode chamber 44. The positive electrode chamber 42 contains a positive electrode 32 and a positive electrode electrolyte 36, and the negative electrode chamber 44 contains a negative electrode 33 and a negative electrode electrolyte 38.

[0046] The positive electrode 32 includes, for example, a positive electrode current collector and a positive electrode composite layer formed on the positive electrode current collector. As the positive electrode current collector, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 32, or a film having such a metal disposed on the surface layer, can be used. From the viewpoints of current collecting properties, mechanical strength, etc., the thickness of the positive electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.

[0047] The positive electrode mixture layer includes a positive electrode active material and may also include a binder, a conductive material, and the like.

[0048] Examples of the positive electrode active material include lithium transition metal oxides containing lithium (Li) and transition metal elements such as cobalt (Co), manganese (Mn) and nickel (Ni). Other examples of the positive electrode active material include transition metal sulfides, metal oxides, and lithium iron phosphate (LiFePO 4 ) and lithium iron pyrophosphate (Li 2 FeP 2 O 7 Lithium-containing polyanion compounds containing one or more transition metals such as sulfur-based compounds (Li 2 S), oxygen, and oxygen-containing metal salts such as lithium oxide. The positive electrode active material is preferably a lithium-containing transition metal oxide, which preferably contains at least one of Co, Mn, and Ni as a transition metal element.

[0049] The lithium transition metal oxide may contain other additive elements besides Co, Mn, and Ni. For example, it may contain aluminum (Al), zirconium (Zr), boron (B), magnesium (Mg), scandium (Sc), yttrium (Y), titanium (Ti), iron (Fe), copper (Cu), zinc (Zn), chromium (Cr), lead (Pb), tin (Sn), sodium (Na), potassium (K), barium (Ba), strontium (Sr), calcium (Ca), tungsten (W), molybdenum (Mo), niobium (Nb), silicon (Si), and the like.

[0050] Specific examples of the lithium transition metal oxide include, for example, Li x CoO 2 , Li x NiO 2 , Li x MnO 2 , Li x Co y Ni 1-y O 2 , Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn 2 O 4 , Li x Mn 2-y M y O 4 , LiMPO 4 , Li 2 MPO 4 F (in each chemical formula, M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0 < x ≦ 1.2, 0 < y ≦ 0.9, 2.0 ≦ z ≦ 2.3). The lithium transition metal oxide may be used alone or in combination of multiple kinds. From the viewpoint of increasing the capacity, it is preferable that the lithium transition metal oxide contains 80 mol% or more of Ni with respect to the total amount of transition metals other than lithium. Also, from the viewpoint of the stability of the crystal structure, the lithium transition metal oxide is Li a Nib Co c Al d O 2 It is more preferable that (0 < a ≤ 1.2, 0.8 ≤ b < 1, 0 < c < 0.2, 0 < d ≤ 0.1, b + c + d = 1).

[0051] As the conductive material, known conductive materials that enhance the electrical conductivity of the positive electrode composite layer can be used. For example, carbon materials such as carbon black, acetylene black, ketjen black, graphite, carbon nanofibers, carbon nanotubes, and graphene can be mentioned. As the binder, known binders that maintain a good contact state between the positive electrode active material and the conductive material and enhance the binding property of the positive electrode active material and the like to the surface of the positive electrode current collector can be used. For example, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), etc. can be mentioned.

[0052] The positive electrode 32 can be manufactured, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, etc. onto the positive electrode current collector, drying and rolling the coating film to form a positive electrode composite layer on the positive electrode current collector.

[0053] The negative electrode 33 includes, for example, a negative electrode current collector and a negative electrode composite layer formed on the negative electrode current collector. As the negative electrode current collector, a foil of a metal stable within the potential range of the negative electrode 33 such as copper, and a film having the metal disposed on the surface layer can be used. From the viewpoints of current collection property, mechanical strength, etc., the thickness of the negative electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.

[0054] The negative electrode composite layer contains a negative electrode active material. Further, the negative electrode composite layer may contain a binder, a conductive material, etc. The same conductive materials and binders as those on the positive electrode 32 side can be used.

[0055] Examples of the negative electrode active material include carbonaceous materials such as natural graphite, artificial graphite, and amorphous carbon such as soft carbon and hard carbon. The negative electrode active material may be any material capable of absorbing and releasing lithium ions, and examples of the negative electrode active material other than the carbonaceous material include elements, alloys, and oxides such as silicon, titanium, germanium, tin, lead, zinc, magnesium, sodium, aluminum, potassium, and indium.

[0056] The negative electrode 33 can be produced by, for example, applying a negative electrode composite slurry containing a negative electrode active material, a binder, etc., onto a negative electrode current collector, drying and rolling the coating to form a negative electrode composite layer on the negative electrode current collector. Alternatively, the negative electrode 33 can be produced by attaching a lithium metal foil onto the negative electrode current collector.

[0057] The separator 34 uses the aluminum foil of this embodiment. That is, the separator 34 uses an aluminum foil having an aluminum foil base material having a porous region formed in the entire thickness direction. As described above, lithium ions pass through the porous region formed in the aluminum foil base material. Therefore, during charging and discharging, lithium ions can be moved between the positive electrode 32 and the negative electrode 33 through the aluminum foil that is the separator 34.

[0058] In addition, the porous region formed in the aluminum foil base material has continuous pores in the thickness direction, in which multiple pores are intricately connected, so that the positive electrode electrolyte 36 is prevented from migrating to the negative electrode chamber 44 through the separator 34 (aluminum foil) and the negative electrode electrolyte 38 is prevented from migrating to the positive electrode chamber 42 through the separator 34 (aluminum foil).

[0059] In addition, it is preferable that an Al-Li alloy is present in the porous region, which increases the lithium ion conductivity of the porous region, and may improve the battery characteristics of the lithium secondary battery 30. Specifically, the initial capacity of the lithium secondary battery 30 may be improved.

[0060] In addition, it is preferable that an Al-Li alloy layer is arranged on one or both sides of the aluminum foil base material so as to cover the porous region. For example, when an Al-Li alloy layer is formed on one side of the aluminum foil base material, even if the electrolyte penetrates into the porous region from one side of the aluminum foil base material where the Al-Li alloy layer is not formed and reaches the other side where the Al-Li alloy layer is formed, the solvent in the electrolyte is blocked by the Al-Li alloy layer, and as a result, it hardly penetrates the separator 34 (aluminum foil). In addition, when an Al-Li alloy layer is formed on both sides of the aluminum foil base material, the solvent in the electrolyte hardly penetrates into the porous region. Therefore, by using an aluminum foil on which an Al-Li alloy layer arranged to cover the porous region is formed on one or both sides of the aluminum foil base material as the separator 34, it is possible to more effectively suppress the movement of the electrolyte for the positive electrode 36 to the negative electrode chamber 44 side through the separator 34, and the electrolyte for the negative electrode 38 to the positive electrode chamber 42 side through the separator 34.

[0061] In this way, by suppressing the movement of the negative electrode electrolyte 38 and the positive electrode electrolyte 36 through the separator 34, reductive decomposition of the electrolyte in the negative electrode chamber 44 and oxidative decomposition of the electrolyte in the positive electrode chamber 42 are suppressed, thereby suppressing the occurrence of side reactions accompanying charging and discharging. This makes it possible to achieve high energy density, high durability, and high output of the lithium secondary battery 30. Note that conventional resin separators are compatible with the electrolyte and it is difficult to form continuous pores that are intricately connected, so that the movement of the electrolyte cannot be sufficiently suppressed and the advantage of using two electrolyte solutions cannot be obtained.

[0062] The thickness of the aluminum foil substrate is, for example, preferably in the range of 1 μm to 200 μm, and more preferably in the range of 5 μm to 20 μm, from the viewpoints of ensuring the strength and flexibility of the aluminum foil while ensuring lithium ion permeability and suppressing the movement of the solvent in the electrolyte.

[0063] The average pore size of the pores constituting the porous region is, for example, preferably in the range of 0.0001 μm to 10 μm, and more preferably in the range of 0.001 μm to 2 μm, from the viewpoints of ensuring lithium ion permeability and suppressing migration of the solvent in the electrolyte while ensuring the strength and flexibility of the aluminum foil.

[0064] When the aluminum foil of this embodiment is used as the separator 34, the positive electrode 32 and the negative electrode 33 need to be separated from the separator 34 so that the positive electrode 32 and the negative electrode 33 are not electrically connected to each other via the separator 34.

[0065] In this embodiment, the positive electrode electrolyte 36 and the negative electrode electrolyte 38 may have the same composition, but it is preferable that each of them has an optimal electrolyte composition in order to achieve high energy density, high durability, and high output. Examples of suitable compositions for the positive electrode electrolyte 36 and the negative electrode electrolyte 38 are given below.

[0066] The solvent used in the positive electrode electrolyte 36 is, for example, + ) is the oxidation potential (vs. Li / Li) of the solvent used in the negative electrode electrolyte 38 + ), for example, it is preferable that it is about 0.5 V to 2.0 V higher. Furthermore, the solvent used in the positive electrode electrolyte 36 has an oxidation potential (vs. Li / Li + ) is the full charge potential of the positive electrode active material (relative to Li / Li + ), for example, the full charge potential (vs. Li / Li + ) by 0.2 V or more. This makes it possible to more effectively suppress the oxidative decomposition of the positive electrode electrolyte 36 in the positive electrode 32.

[0067] Preferred examples of the solvent used in the positive electrode electrolyte 36 include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate; fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC); fluorinated chain carbonates such as trifluorodimethyl carbonate (TFDMC); and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).

[0068] The solvent used in the negative electrode electrolyte 38 is preferably, for example, a solvent that is unlikely to undergo reductive decomposition at the negative electrode 33. Examples of the solvent include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ether, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl Preferred are chain ethers such as diphenyl ether, butylphenyl ether, pentylphenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0069] The electrolyte salts used in the positive electrode electrolyte 36 and the negative electrode electrolyte 38 may be the same or different as long as they are lithium salts generally used in lithium secondary batteries. For example, LiClO 4 , LiBF 4 , LiPF 6 , LiAlCl 4 , LiSbF 6 , LiSCN, LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiB 10 Cl 10 , lithium lower aliphatic carboxylate, LiCl, LiBr, LiI, Li(P(C 2 O 4 )F 4 , LiPF 6-x (C n F 2n+1 )x(1 < x < 6, n is 1 or 2), lithium chloroborane, borate salts, imide salts, etc. may be mentioned. As borate salts, Li[B(C 2 O 4 ) 2 , Li[B(C 2 O 4 )F 2 , Li 2 B 4 O 7, lithium bis(1,2-benzenedioleate(2-)-O,O')borate, lithium bis(2,3-naphthalenediolate(2-)-O,O')borate, lithium bis(2,2'-biphenyldioleate(2-)-O,O')borate, lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate, and the like. Examples of imide salts include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(perfluoroethanesulfonyl)imide (LiBETI), lithium (perfluoroethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide (LiFTI), and the like. The electrolyte salt may be used alone or in combination of two or more of these.

[0070] The concentration of the electrolyte salt in the positive electrode electrolyte 36 is, for example, preferably 0.5 mol / L to 3.0 mol / L, and more preferably 0.8 mol / L to 1.8 mol / L. The concentration of the electrolyte salt in the negative electrode electrolyte 38 is, for example, preferably 0.5 mol / L to 3.0 mol / L, and more preferably 0.8 mol / L to 1.8 mol / L.

[0071] Below, modified examples of the battery structure when the aluminum foil of this embodiment is used as a separator are shown.

[0072] Fig. 7 is a schematic cross-sectional view showing another example of a battery structure when the aluminum foil of this embodiment is used as a separator. The lithium secondary battery of this embodiment may adopt a battery structure in which, instead of the above-mentioned electrolyte for the positive electrode and electrolyte for the negative electrode, a gel electrolyte layer 46 for the positive electrode is disposed between the positive electrode 32 and the separator 34 which is the aluminum foil of this embodiment, and a gel electrolyte layer 48 for the negative electrode is disposed between the negative electrode 33 and the separator 34 which is the aluminum foil of this embodiment, as shown in Fig. 7. The thickness of the gel electrolyte layer 46 for the positive electrode and the gel electrolyte layer 48 for the negative electrode is, for example, about 5 µm to 100 µm.

[0073] The positive electrode gel electrolyte layer 46 can be formed, for example, by applying a precursor solution obtained by adding a polymer precursor, a polymerization initiator, and the like to the above-mentioned positive electrode electrolyte to the positive electrode mixture layer, and then proceeding with a polymerization reaction under appropriate conditions to gel the mixture. The negative electrode gel electrolyte layer 48 can be formed in the same manner.

[0074] The polymerization temperature during gelation may be appropriately selected, for example, about 80 to 140° C. The polymerization time may also be appropriately selected, for example, about 5 minutes to 3 hours. The "polymerization reaction" referred to here may be any reaction that can contribute to the gelation (hardening) of the precursor solution, such as a crosslinking reaction, a condensation reaction, etc.

[0075] The polymer precursor may be either a multifunctional polymer precursor or a monofunctional polymer precursor, but a polymer precursor having two or more polymerizable (crosslinkable) functional groups (a multifunctional polymer precursor) is preferred. Specific examples include ethylene oxide (EO), propylene oxide (PO), acrylonitrile (AN), vinylidene fluoride (VDF), etc. Typically, a polymer precursor having a thermally polymerizable (thermally crosslinkable) functional group is used.

[0076] The polymerization initiator can be appropriately selected and used depending on the type of polymer precursor used. Typically, a thermal polymerization initiator is used. As the thermal polymerization initiator, various conventionally known initiators such as azo-based and peroxide-based initiators can be used. Examples of preferred polymerization initiators include azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO).

[0077] FIG. 8 is a schematic cross-sectional view showing another example of a battery structure when the aluminum foil of this embodiment is used as a separator. In the lithium secondary battery of this embodiment, as shown in FIG. 8, a porous sheet 50 may be disposed between the positive electrode 32 and the separator 34 which is the aluminum foil of this embodiment, and between the negative electrode 33 and the separator 34 which is the aluminum foil of this embodiment. It is desirable that the porous sheet 50 has high electrical insulation and a function of permeating lithium ions. Specific examples of the porous sheet 50 include a microporous thin film, a woven fabric, a nonwoven fabric, and the like. Examples of the material of the porous sheet 50 include olefin-based resins such as polyethylene and polypropylene, polyamide, polyamideimide, cellulose, and the like. The porous sheet 50 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin-based resin. It may also be a multilayer body including a polyethylene layer and a polypropylene layer, and may be a porous sheet 50 having a material such as an aramid-based resin or ceramic applied to the surface of the porous sheet 50.

[0078] The porous sheet 50 disposed between the positive electrode 32 and the separator 34 which is the aluminum foil of this embodiment may be impregnated with the above-mentioned electrolyte for the positive electrode. The porous sheet 50 disposed between the negative electrode 33 and the separator 34 which is the aluminum foil of this embodiment may be impregnated with the above-mentioned electrolyte for the negative electrode.

[0079] The positive electrode mixture layer constituting the positive electrode 32 is preferably a clay-like wet film containing a positive electrode active material, a binder, a conductive material, and the above-mentioned positive electrode electrolyte. The positive electrode mixture layer is obtained by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, a positive electrode electrolyte, and the like, onto a positive electrode current collector. Similarly, the negative electrode mixture layer constituting the negative electrode 33 is preferably a clay-like wet film containing a negative electrode active material, a binder, and a negative electrode electrolyte. The negative electrode mixture layer is obtained by applying a negative electrode mixture slurry containing a negative electrode active material, a binder, a negative electrode electrolyte, and the like, onto a negative electrode current collector.

[0080] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0081] [Aluminum foil manufacturing] Using the manufacturing apparatus shown in FIG. 4, an oxidation current was passed through both sides of an aluminum foil substrate having a thickness of 12 μm under the following conditions.

[0082] Electrolyte: LiTFSI / PC=1 / 10 (molar ratio) Oxidation current density: 10μA / cm 2 Processing time: 1 hour When the cross section of the treated aluminum foil substrate was observed by SEM, it was confirmed that a porous region was formed throughout the thickness of the aluminum foil substrate. This was designated aluminum foil A.

[0083] Using the manufacturing apparatus shown in FIG. 4, a reducing current was passed through one surface of an aluminum foil substrate, and an oxidizing current was passed through the other surface opposite to the one surface, under the following conditions.

[0084] Electrolyte: LiTFSI / PC=1 / 10 (molar ratio) Reduction current density: 10μA / cm 2 Oxidation current density: 10μA / cm 2 Processing time: 332 hours When the cross section of the aluminum foil substrate after the treatment was confirmed by SEM, it was confirmed that a porous region was formed throughout the entire thickness direction of the aluminum foil substrate. In addition, a coating layer was confirmed to be arranged on the other side of the aluminum foil substrate so as to cover the porous region. When the components of this coating layer and the porous region were confirmed by Auger electron spectroscopy, it was confirmed that the coating layer was formed from an Al-Li alloy and that the porous region contained an Al-Li alloy. This was designated as aluminum foil B.

[0085] <Example 1> [Negative electrode] The aluminum foil A was cut to a predetermined electrode size and used as a negative electrode.

[0086] [Positive electrode] LiCoO as a positive electrode active material 2 The positive electrode mixture slurry was prepared by mixing the carbon black as a conductive material and the PVdF as a binder in a mass ratio of 94:3:3 in NMP. The positive electrode mixture slurry was then applied onto a positive electrode current collector made of Al foil, the coating was dried, and then rolled with a rolling roller. The positive electrode mixture slurry was then cut into a predetermined electrode size to obtain a positive electrode.

[0087] [Electrolyte] LiPF 6 and PC, LiPF 6 The solution mixed at a molar ratio of 1 / 10 was used as an electrolyte solution.

[0088] [Test cell] The electrode assembly in which the positive electrode and the negative electrode were arranged facing each other with a polypropylene separator (Celgard, #3401) in between, and the above electrolyte were placed in a cup-shaped battery case, and the battery case was sealed with a sealing plate via a gasket disposed at the opening of the battery case, to prepare a test cell.

[0089] <Example 2> A test cell was prepared in the same manner as in Example 1, except that the aluminum foil B was cut to a predetermined size and used as the negative electrode.

[0090] <Comparative Example 1> A test cell was prepared in the same manner as in Example 1, except that an aluminum foil substrate without a porous region was used as the negative electrode.

[0091] [Charge / discharge test] The test cells of Examples 1 and 2 and Comparative Example 1 were charged at a constant current of 0.01 C in an environment of 25° C. until the battery voltage reached 4.3 V. Then, the cells were discharged at a constant current of 0.01 C until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 20 times.

[0092] The charge-discharge efficiency ((discharge capacity / charge capacity)×100) at the 20th cycle was 93.1% for Example 1, 93.3% for Example 2, and 92.4% for Comparative Example 1. From these results, Examples 1 and 2, in which an aluminum foil having a porous region formed over the entire thickness direction of the aluminum foil base material was used as the negative electrode, can suppress the deterioration of the charge-discharge cycle characteristics compared to Comparative Example 1, in which an aluminum foil having no porous region formed was used as the negative electrode.

[0093] The initial charge-discharge efficiency was 74.7% in Example 1, 74.8% in Example 2, and 74.4% in Comparative Example 1. From these results, it can be seen that the initial charge-discharge efficiency can be improved by using an aluminum foil as a negative electrode, in which an Al-Li alloy exists in the porous region and an Al-Li alloy layer is disposed on one side of the aluminum foil base material so as to cover the porous region, as in Example 2.

[0094] <Example 3> Both chambers of the manufacturing equipment shown in Figure 4 were filled with an electrolyte of LiTFSI / PC = 1 / 10 (molar ratio), and a current of 1 mA / cm was applied to both sides of an aluminum foil with a thickness of 12 μm. 2 An oxidation current of this value was passed for 1 second to obtain aluminum foil C having a porous region throughout its thickness.

[0095] As shown in FIG. 6, a test cell was prepared in which the inside of the container was separated into a positive electrode chamber and a negative electrode chamber by a separator, the positive electrode chamber contained a positive electrode (working electrode) and a positive electrode electrolyte, and the negative electrode chamber contained a negative electrode (counter electrode) and a negative electrode electrolyte. The above-mentioned aluminum foil C was used as the separator. A platinum mesh electrode was used as the positive electrode, and a lithium metal electrode was used as the negative electrode. The positive electrode electrolyte was a propylene carbonate (PC) solvent with 10 moles of LiTFSI dissolved therein at 1 mole, and the negative electrode electrolyte was a diethylene glycol dimethyl ether (diglyme) solvent with 10 moles of LiTFSI dissolved therein at 1 mole.

[0096] <Example 4> Both chambers of the manufacturing equipment shown in Figure 4 were filled with an electrolyte of LiTFSI / PC = 1 / 10 (molar ratio), and a current of 1 mA / cm was applied to one side of an aluminum foil with a thickness of 12 μm. 2 of reduction current, 1mA / cm on the other side 2 By passing an oxidation current of 10 hours, an aluminum foil D having a porous region in the entire thickness direction and an Al-Li alloy layer was obtained. A test cell was prepared in the same manner as in Example 3, except that the aluminum foil D was used as a separator.

[0097] <Comparative Example 2> A test cell was prepared in the same manner as in Example 3, except that a polypropylene separator (manufactured by Celgard, #3401) was used.

[0098] In the test cells of Examples 3 and 4 and Comparative Example 2, a voltage of 4.3 V was applied between the positive electrode (working electrode) and the negative electrode (counter electrode) for 50 hours to measure the current flowing between the positive electrode and the negative electrode. As a result, in the test cells of Examples 3 and 4, the current value remained below 0.1 μA, while in the test cell of Comparative Example 2, the current value remained at about 0.6 μA.

[0099] In addition, a voltage of 4.5 V was applied between the positive electrode (working electrode) and the negative electrode (counter electrode) for 50 hours to measure the current value between the two electrodes in the test cells of Examples 3 and 4 and Comparative Example 2. As a result, the current value remained at 0.2 μA in the test cell of Example 3, and at 0.18 μA or less in the test cell of Example 4, while the current value remained at about 1 μA in the test cell of Comparative Example 2.

[0100] In addition, a voltage of 4.7 V was applied between the positive electrode (working electrode) and the negative electrode (counter electrode) for 100 hours to measure the current value between the two electrodes in the test cells of Examples 3 and 4 and Comparative Example 2. As a result, the current value remained at 0.25 μA in the test cell of Example 3, and at 0.2 μA or less in the test cell of Example 4, while the current value remained at about 6 μA in the test cell of Comparative Example 2.

[0101] Thus, in Examples 3 and 4 in which an aluminum foil having a porous region formed in the entire thickness direction of the aluminum foil base material was used as a separator, the current value between the two electrodes remained at a very low value even when a high voltage was applied. From this result, it can be said that in Examples 3 and 4, the solvent in the electrolyte for the negative electrode in the negative electrode chamber was prevented from moving to the positive electrode chamber through the separator, and the electrolyte in the positive electrode chamber was hardly oxidized and decomposed. This makes it possible to achieve high energy density, high durability, and high output of the lithium secondary battery. On the other hand, in Comparative Example 2 in which a polypropylene separator was used, the current value between the two electrodes remained at a high value when a high voltage was applied, compared with Examples 3 and 4. From this result, it can be said that in Comparative Example 2, the solvent in the electrolyte for the negative electrode in the negative electrode chamber could not be prevented from moving to the positive electrode chamber through the separator, and the electrolyte in the positive electrode chamber was oxidized and decomposed in Examples 3 and 4.

[0102] In Examples 3 and 4, the platinum mesh was LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 The positive electrode active material was replaced with LiPF 6 When the electrolyte solution was replaced with a solution of 0.1% by weight of 0.1% by weight of 1 / PC (molar ratio), a charge-discharge reaction (voltage range: 2.5 to 4.7 V) was observed due to the movement of lithium ions between the positive and negative electrodes. In other words, the aluminum foils used in Examples 3 and 4 have lithium ion permeability and can be used as separators. [Explanation of symbols]

[0103] 1 Manufacturing equipment 10 Room 1 11 Room 2 13 Electrolytic cell 14,15 Electrolyte 16,17 Polar opposites 18 Aluminum foil substrate 20,30 Lithium secondary battery 21 Battery case 22,32 positive electrode 23,33 negative electrode 24,34 Separator 25 Gasket 26 Sealing plate 27 Electrolyte 36 Electrolyte for positive electrode 38 Electrolyte for negative electrode 40 Containment Container 42 Positive electrode chamber 44 Anode chamber 46 Positive electrode gel electrolyte layer 48 Gel electrolyte layer for negative electrode 50 Porous sheet 100 Aluminum foil 100a Aluminum foil substrate 100b porous area 100c Al-Li alloy layer

Claims

1. An aluminum foil substrate having a porous region, The porous region is formed over the entire thickness direction of the aluminum foil base material.

2. 2. The separator for a lithium secondary battery according to claim 1, wherein an Al-Li alloy is present in the porous region.

3. 3. The lithium secondary battery separator according to claim 1, further comprising an Al-Li alloy layer disposed on one or both sides of the aluminum foil substrate so as to cover the porous region.

4. 4. The separator for a lithium secondary battery according to claim 1, wherein the average pore size of the pores present in the porous region is in the range of 0.00001 μm to 10 μm.

5. A lithium secondary battery comprising: a positive electrode; a negative electrode; and the separator for a lithium secondary battery according to any one of claims 1 to 4, the separator being provided between the positive electrode and the negative electrode, the positive electrode and the negative electrode being spaced apart from the separator for a lithium secondary battery.

6. 6. The lithium secondary battery according to claim 5, further comprising a gel electrolyte layer between the positive electrode and the separator for the lithium secondary battery and between the negative electrode and the separator for the lithium secondary battery.

Citation Information

Patent Citations

  • Organic electrolytic battery using aluminum-lithium alloyed porous body for negative electrode

    JP1989063268A

  • Lithium secondary battery

    JP1993021091A

  • Separator and lithium secondary battery

    JP1996180853A

  • Precursor battery and nonaqueous electrolyte secondary battery

    JP2005294013A

  • Separator for battery, battery using this, vehicle using this, and battery mounted equipment

    JP2010219012A